2015
DOI: 10.3389/fpls.2015.00277
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate depletes glutathione and upregulates expression of glutathione S-transferases in Arabidopsis thaliana

Abstract: Allyl isothiocyanate (AITC) is a phytochemical associated with plant defense in plants from the Brassicaceae family. AITC has long been recognized as a countermeasure against external threats, but recent reports suggest that AITC is also involved in the onset of defense-related mechanisms such as the regulation of stomatal aperture. However, the underlying cellular modes of action in plants remain scarcely investigated. Here we report evidence of an AITC-induced depletion of glutathione (GSH) and the effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 58 publications
(74 reference statements)
4
43
0
1
Order By: Relevance
“…Although the interaction of AITC with GSSG was demonstrated in in vitro experiments, the GSH reversible depletion and consequent ROS accumulation has been previously observed in AITC treated A. thaliana seedlings . This action previously suggested a role of the glutathione system in the detoxification/control of isothiocyanates in plant tissue, in accordance with findings in insects and mammalian cells . Nonetheless, despite the different system and model plant considered in the other studies, the concentration used in the present study was much lower than that used for other in vitro/in vivo investigations and this might have played a critical role in expressing its pro‐ or anti‐oxidant action and biological effects .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Although the interaction of AITC with GSSG was demonstrated in in vitro experiments, the GSH reversible depletion and consequent ROS accumulation has been previously observed in AITC treated A. thaliana seedlings . This action previously suggested a role of the glutathione system in the detoxification/control of isothiocyanates in plant tissue, in accordance with findings in insects and mammalian cells . Nonetheless, despite the different system and model plant considered in the other studies, the concentration used in the present study was much lower than that used for other in vitro/in vivo investigations and this might have played a critical role in expressing its pro‐ or anti‐oxidant action and biological effects .…”
Section: Resultssupporting
confidence: 75%
“…Such a multifunctional role is also supported by a genome scale transcriptional profiling of A. thaliana exposed to AITC, which shows the induction of a rapid response involving numerous processes considered to be part of a plant defence strategy . In addition, AITC has been seen to induce, in Arabidopsis , cellular reversible glutathione depletion and up‐regulation of genes that encode glutathione S ‐transferase, which have been suggested as the plant isothiocyanate detoxification/control mechanism . At the same time, in small berry fruit, AITC has shown not only to reduce decay, but also to exert a pro‐oxidant action detected by an increased ROS production which, again, has been suggested as a possible plant defence mechanism induced by AITC …”
Section: Introductionmentioning
confidence: 90%
“…A study by Overby et al showed that isothiocyanates disrupted microtubules in Arabodopsis thalinia and in AY-27 rat bladder cancer cells suggesting that plant and mammalian cells share isothiocyante-mediated antigrowth mechanisms. [142] Additionally, SFN was also shown to induce mitotic arrest, however, not in the G2 phase of the cell cycle. Park et al revealed that 5637 human bladder cancer cells treated with SFN underwent caspase-dependent apoptosis via accumulation of ROS.…”
Section: Modulation Of Cell Cycle and Apoptosismentioning
confidence: 99%
“…This observation suggests that GSH depletion is not necessary for the antifungal activity of HREO. The induction of GST (Table ), an enzyme which catalyses the reaction between GSH and ITCs , at low‐HREO concentration, as well as the depletion of GSH pools at high concentration, suggest that HREO reacted with GSH in vivo but cells could counterbalance this process at low‐HREO levels. Not surprisingly CDNB, a well known chemical which decreases the GSH pool in C. albicans , showed strong synergism with HREO (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It induces oxidative stress most likely due to its effect on mitochondrial functions . Cells can detoxify HREO components by GSH . GSH reacts spontaneously with ITCs, and GST may also catalyze this reaction.…”
Section: Discussionmentioning
confidence: 99%